Just a second : a different way to look at time - Jenkins, Steve, 1952- (Boston : Houghton Mifflin Books for Children, 2011)
Describes a series of events in the natural world to provide an exploration of how people think about time.
Includes bibliographical references.
4.7
K-3
Keywords: Time -- Juvenile literature; Nature -- Juvenile literature; Time; Nature; Time; Nature; JUVENILE NONFICTION / Concepts / Counting & Numbers; JUVENILE NONFICTION / Science & Nature / General (see also headings under Animals or Technology); JUVENILE NONFICTION / Animals / General; JUVENILE NONFICTION / General; Time; Time measurements; Nature